Sobrecarga do cuidador informal em cuidados paliativos - Ana Cláudia Dias Faria (2024)
The combination of an ageing population and an increasing prevalence of advanced, disabling and life-threatening illnesses has a negative effect on the quality of life of patients. Palliative care (PC) plays a pivotal role in the lives of these individuals, providing comprehensive care with the objective of optimising comfort and quality of life while upholding human dignity. Palliative care intervention is based on four fundamental pillars: symptom control, family support, teamwork and communication. Furthermore, the patient's family should be included in the care process and should themselves be the focus of nursing care. Despite the lack of preparation and training typically afforded to carers, they frequently assume the role of primary care providers in situations of advanced and life-threatening illness. Consequently, they are at elevated risk of caregiver burden. It is incumbent upon the healthcare professionals accompanying the patient and family to comprehend their needs, concerns and apprehensions and to furnish the requisite support. The phenomenon of carer's burden can be attributed to a number of adverse changes in the life of the carer, which are a direct consequence of the demands associated with the care of a family member. In recent years, the home care model has emerged as the preferred approach to supporting chronically ill patients, with the objective of enabling patients to remain in the company of their families. It is therefore evident that home palliative care teams play a pivotal role in providing guidance and support to caregivers, thereby enhancing safety and independence in care, which are crucial factors in reducing caregiver burden. This report is the result of a professional placement with a community palliative care support team, undertaken as part of the Master's in Palliative Care. The objective is to delineate the learning process and skill acquisition during the placement, with reference to the topics covered in the first year of the Master's programme. With regard to the research area, given the relevance of carer burden in this context, a scoping review was conducted on this topic. It can be concluded that the issue of caregiver burden in palliative care is a current reality and represents a challenge for healthcare professionals. It is crucial to gain a deeper comprehension and characterization of this phenomenon and its associated factors, with the aim of enabling early intervention in its prevention or control. This will help to minimise its impact on the lives of both the caregiver and the patient. The completion of this professional internship enabled the master's student to become aware of several important issues in the context of home care. It also facilitated the acquisition of specific skills in caring for palliative patients, based on the principles of palliative care.